Microturbocharger with Air Foil Bearings for a 100-W Class Micro Power System and Improvement of Rotordynamic Performance - Lee, Yong-Bok; Kwak, Yong-Suk; Chung, Jin Taek; Sim, Kyuho (TAYLOR & FRANCIS INC, 2011)
This article presents the experimental investigation of a microturbocharger supported on bump-type air foil bearings (AFBs) for a 100-W power generation. The microturbocharger was designed via thermodynamic cycle analyses as well as rotordynamic analyses and constructed using a centrifugal compressor and turbine with tip diameter of 10 mm. The tests for AFBs at rotating speeds up to 410 krpm driven by air showed a large subsynchronous motion at 100 Hz. However, AFBs with an additional viscoelastic film eliminated the subsynchronous response due to increased damping by the viscoelastic film. The compressor performance was evaluated numerically and experimentally.
Keywords: JOURNAL BEARINGS